2017
DOI: 10.1016/j.jspd.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Proximal Junctional Kyphosis in Adolescent Idiopathic Scoliosis—The Pelvis and Other Considerations

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 11 publications
8
75
3
Order By: Relevance
“…Kim [1]and Wang [2] defined PJK in AIS patients as both an increase of > 10° in kyphosis between the UIV and the UIV + 2 and the final PJA greater than or equal to 10°, which was widely used in AIS patients [1,2,4,5] and was chosen in our study. Previous studies have reported incidences of PJK after surgery for Lenke 5C AIS of 8.49% [4]. Sun et al [3] reported that an increase of PJK larger than 10°o ccurred after selective fusion in 17.1% of patients with Lenke 5C AIS at 2 years postoperatively, which is comparable to the PJK incidence found in the present study (23.0%).…”
Section: Proximal Junctional Kyphosis and Extendned Fusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kim [1]and Wang [2] defined PJK in AIS patients as both an increase of > 10° in kyphosis between the UIV and the UIV + 2 and the final PJA greater than or equal to 10°, which was widely used in AIS patients [1,2,4,5] and was chosen in our study. Previous studies have reported incidences of PJK after surgery for Lenke 5C AIS of 8.49% [4]. Sun et al [3] reported that an increase of PJK larger than 10°o ccurred after selective fusion in 17.1% of patients with Lenke 5C AIS at 2 years postoperatively, which is comparable to the PJK incidence found in the present study (23.0%).…”
Section: Proximal Junctional Kyphosis and Extendned Fusionmentioning
confidence: 99%
“…To reduce the incidence of PJK, it is critical to restore and maintain normal TK [1,2,3,5]. Important risk factors for PJK in AIS include reduction of TK and large preoperative TK [2,4,5].…”
Section: Proximal Junctional Kyphosis and Extendned Fusionmentioning
confidence: 99%
See 3 more Smart Citations